2009
DOI: 10.1111/j.1708-8240.2009.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Repair Bond Strength of a Nano‐filled Hybrid Resin: Effect of Surface Treatments and Bonding Agents

Abstract: Surface treatment with a diamond bur plus a proper adhesive agent is a simple, efficient, and cost-effective procedure for enhancing the shear bond strength of a repaired nano-hybrid resin composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
2
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 26 publications
8
71
2
12
Order By: Relevance
“…13,[26][27][28] In this study, it was interesting to see quite different results from the two acid etching subgroups. When repaired with Filtek Z250 (group 2M), the 35% phosphoric acid was able to produce microtensile bond strength values comparable to the cohesive strength of the silorane composite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[26][27][28] In this study, it was interesting to see quite different results from the two acid etching subgroups. When repaired with Filtek Z250 (group 2M), the 35% phosphoric acid was able to produce microtensile bond strength values comparable to the cohesive strength of the silorane composite.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,[14][15][16][17] The bonding of new to aged composite mostly depends on micromechanical interaction, but chemical bonding is also to be taken into consideration. [18][19][20] In a clinical situation, there may be no information about the chemical composition of the existing resin composite restorations. Understanding how to repair existing silorane restorations is critical because there is limited information regarding repair protocols of silorane composite.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers agreed that the bonding of new to old composite is mainly micromechanical, 3,9,28 although chemical bonding cannot be disregarded. 29 There are no available data in the literature on the repair bond strength considered adequate enough to survive in occlusal function. 30 Therefore, many studies 20,30,31 have suggested that the cohesive strength of the intact unrepaired material should be taken into consideration as a control in the evaluation of the repair bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical retention can be provided with some surface treatment modalities, such as roughening the surface with a coarse diamond bur [11][12][13][14][15][16][17][18][19], a rotary cutting instrument [20][21][22][23][24], a sandblasting or air-abrasion system with aluminium oxide powder [11,25], or phosphoric [26] or hydrofluoric acid [18].…”
Section: Introductionmentioning
confidence: 99%
“…Surface treatment on the fractured surface of composite resin materials must be performed to obtain high bond strength between the materials. Although there is a great deal of information about the effect of several treatment methods on the bonding strength of composite restorations [18,20,27,[31][32][33][34][35][36][37][38][39][40][41][42], very limited data are available on the use of surface treatment of CAD/CAM resin-based materials [26,37,[43][44][45][46] to enhance their repair bond strength.…”
Section: Introductionmentioning
confidence: 99%